FEBRILE CONVULSIONS IN CHILDREN: RELATIONSHIP OF FAMILY HISTORY TO TYPE OF CONVULSIONS AND AGE AT PRESENTATION - Siddiqui, Tahir Saeed (Journal of Ayub Medical College Abbottabad, 2002)
Background: Febrile Convulsions are the commonest cause of convulsions in children under five years of age. Present study was conducted to know relationship of positive family history of convulsions to the type of febrile convulsions and age of presentation. Methods: This study was carried out in the Department of Paediatrics, Hayat Shaheed Teaching Hospital Peshawar from June 1999 to June 2000. Data of all children with febrile convulsions were recorded on special proforma. Convulsions were labelled as febrile by excluding infections of central nervous system in developmentally normal children on the basis of history, examination and relevant laboratory investigations. Results: In 30% children there was positive family history of febrile convulsions and febrile convulsions occurred at earlier age in these children. Febrile convulsions were complex in 35% of cases and out of these there was positive family history of convulsions in 29% of children. As a whole 44% of children had first febrile convulsions below 12 months of age and 56% above 12 months of age. Conclusion: Majority of febrile convulsions occurred in first two years of life. Initial febrile convulsions of simple type are more common in children with positive family history of convulsions, in whom first febrile convulsions tend to occur at earlier age. Further, complex febrile convulsions are more common when age at presentation is less than 12 months.